PENGARUH KOMITE AUDIT (AUDIT MEETING), MANAGERIAL DIRECTOR TERHADAP KONSERVATISME AKUNTANSI (Studi pada Industri Ritel yang Terdaftar di Bursa Efek Indonesia Tahun 2012-2016). - Fitri Anjani; Dudi Pratomo; Kurnia Kurnia (Jurnal Akuntansi Bisnis dan Ekonomi, 2018)
Conservatism is the prudence principle in the preparation of financial reporting in which the company is not rush to recognizing revenue and profit, as well as immediately, recognize cost and loss that have the possibility of occurring. The prudence principle is referred to accounting conservatism. This study aimed to obtain empirical evidence of the influence of the audit committee, managerial ownership, foreign ownership, and independent director to accounting conservatism. The population in this study is a sub-company retail industry sector listed on the Indonesia Stock Exchange in 2012-2016. Mechanical sample selection using purposive sampling and acquired 5 companies by 5 years in order to get 25 samples was observed. Model analysis of the data in this research is panel data regression using Software Eviews 9.0. This study shows that independent variables such as the audit committee, managerial ownership, foreign ownership, and independent director simultaneously affect the dependent variable accounting conservatism. In partial of variable audit committee significant positive effect on accounting conservatism, variable independent director significant negative effect on accounting conservatism. Meanwhile, the variable managerial ownership and foreign ownership no significant effect on accounting conservatism. Conclusions of this research is the audit committee and independent director significant effect on accounting conservatism, while managerial ownership and foreign ownership has no effect and can reduce the accounting conservatism at the company. Suggestions for the company is to increase the amount of managerial share ownership and for the investor to see the company that has a high proportion of foreign share ownership. As for further research, can use other measurement methods to measure conservatism as using Zhang or Basu method. From the test results obtained partial results showing variable levels of financial difficulty with negative direction have a significant effect on accounting conservatism. Variable litigation risk and growth opportunities no significant effect on accounting conservatism.